2022
DOI: 10.1186/s12864-022-08413-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics of plant pathogenic Diaporthe species and transcriptomics of Diaporthe caulivora during host infection reveal insights into pathogenic strategies of the genus

Abstract: Background Diaporthe caulivora is a fungal pathogen causing stem canker in soybean worldwide. The generation of genomic and transcriptomic information of this ascomycete, together with a comparative genomic approach with other pathogens of this genus, will contribute to get insights into the molecular basis of pathogenicity strategies used by D. caulivora and other Diaporthe species. Results In the present work, the nuclear genome of D. caulivora i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(46 citation statements)
references
References 130 publications
(107 reference statements)
3
43
0
Order By: Relevance
“…The proportion of CAZymes in the D. amygdali secretome (29.1%) is consistent with previous reports in other Diaporthe species, such as D. capsici and D. citri (30.7%), D. caulivora (30.6%), and D. longicolla (31.4%), emphasizing the importance of CAZymes in Diaporthe pathogenicity [ 16 ]. Nevertheless, the proportion of CAZymes in the secretome of D. eres CBS 160.32 was estimated at 5.4%, which is low when compared with the abovementioned species (average = 30.5%).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The proportion of CAZymes in the D. amygdali secretome (29.1%) is consistent with previous reports in other Diaporthe species, such as D. capsici and D. citri (30.7%), D. caulivora (30.6%), and D. longicolla (31.4%), emphasizing the importance of CAZymes in Diaporthe pathogenicity [ 16 ]. Nevertheless, the proportion of CAZymes in the secretome of D. eres CBS 160.32 was estimated at 5.4%, which is low when compared with the abovementioned species (average = 30.5%).…”
Section: Discussionsupporting
confidence: 89%
“…These genomes, whose annotations are publicly available, were used to perform a comparison of GC content, genome size, BUSCO completeness, predicted proteins, and abundance of CAZymes and BGCs. These taxa include mainly pathogens of citrus [ 17 ], grapevine [ 22 ], soybean [ 16 , 21 ], sunflower [ 20 ], sweet potato [ 23 ], and walnut [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As TEF1 is a single copy gene (Hasegawa et al, 2010), this was an expected result, comparable to the sensitivity reported for other TEF1 based real‐time PCR assays, e.g., of Fusarium oxysporum and Monilinia kusanoi assays (Dharmaraj et al, 2021; Haegi et al, 2013). While there are no genome data available for D. vaccinii , using the average known genome size of other Diaporthe species (.06 pg) (Mena et al, 2022), it is estimated that the real‐time PCR assay could detect approximately less than 20 haploid hyphal cells.…”
Section: Discussionmentioning
confidence: 99%